A5_3 Are the Boots a Lie? - Allison, Hayley Jane; Leyser, Roger Paul; Penney, Jordan Iain; Lipscombe, Giles Christopher (Physics Special Topics, 2014)
An investigation is described regarding the spring constant of the material used to create the boots worn by the leading character in the game ‘Portal’. Within the game, the boots allow the character to fall from any height without injury. It is found that this is a possible feat using a spring constant of approximately 1 Nm-1 but the design must differ considerably from that depicted in the game.